2017
DOI: 10.15171/npj.2017.53
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of microRNA profile of kidney biopsies of patients with lupus nephritis

Abstract: Background: The changes in some epigenetic elements such as microRNAs result in aberrant immune responses leading to production and secretion of nephritogenic autoantibodies as the main fundament of lupus nephritis (LN).Objectives: The present study aimed to assess the miRNA profile of kidney biopsies in patients with LN with the purpose of describing the critical role of these elements in LN creation. Patients and Methods:In this case-control single center study 11 patients who suffered LN (as the case group)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Accordingly, 66 miRNAs were found differentially expressed (36 upregulated and 30 downregulated) in lupus nephritis (9). In a recent study, in 11 Iranian patients with lupus nephritis (LN), we found, no relationship between intrarenal expression of miRNAs 638,146 a, 198,731 and appearance of disease was existed (10). Expression of specific intrarenal miRNAs is established in glomerulosclerosis (mir-200 a,b), tubulointerstitial nephritis and also diabetic nephropathy (mir-192) (11).…”
mentioning
confidence: 88%
“…Accordingly, 66 miRNAs were found differentially expressed (36 upregulated and 30 downregulated) in lupus nephritis (9). In a recent study, in 11 Iranian patients with lupus nephritis (LN), we found, no relationship between intrarenal expression of miRNAs 638,146 a, 198,731 and appearance of disease was existed (10). Expression of specific intrarenal miRNAs is established in glomerulosclerosis (mir-200 a,b), tubulointerstitial nephritis and also diabetic nephropathy (mir-192) (11).…”
mentioning
confidence: 88%
“…The miR profile in kidney biopsy samples from LN patients was first reported in 2009, though this was a small study with only 5 patients with inactive, class II LN [ 58 ]. Since then, a plethora of studies have shown that many miRs are differentially expressed in various renal cells in both human subjects and murine models, with only limited overlap with the miR signature in the systemic circulation [ 49 , 51 , 59 , 60 ]. LN is a heterogeneous disease involving immune-mediated injury to different cell types in the kidney, including mesangial cells and podocytes in the glomeruli, tubulointerstitial cells as well as vascular smooth muscle and endothelial cells, among others.…”
Section: Mirs In the Kidney Tissuementioning
confidence: 99%